EXPERIMENTAL EVALUATION OF THE REMOVAL EFFICIENCY OF SO2 IN A SPRAY TOWER USING DIFFERENT SPRAY NOZZLES - Codolo, M. C.; Bizzo, W. A. (Revista de Engenharia Térmica, 2013)
This work presents an experimental evaluation of the removal efficiency of SO2 in a spray tower. The experiments were carried out in different conditions, varying gas velocity and using different sprays nozzles. The influence of the height of tower on the removal efficiency was evaluated through experiments inside spray tower. In this study was used two sets of five nozzles, with diameter of orifice of 2.4 and 3.2 mm, and only one nozzle with diameter of orifice of 5.6 mm. The results showed the influence of the gas velocity and L/G ratio in the removal efficiency, the influence of the gas velocity on the volumetric gas side mass transfer coefficient and the influence of the height of the tower in the removal efficiency.